Model of Implementing Bus Rapid Transit (BRT) Mass Public Transport Policy in DKI Jakarta Province, Indonesia - Sunardi Manampiar Sinaga; Muchlis Hamdi; Sadu Wasistiono; Sampara Lukman (International Journal of Science and Society, 2020)
The purpose of this study is to find a model for implementing policies on the development of Bus Rapid Transit (BRT) based on mass public transportation in DKI Jakarta Province, Indonesia. This research uses qualitative methods with data collection techniques such as observation, in-depth interviews and literature study. Policy choices for developing mass public transportation based on BRT seem to remain a rational choice for overcoming traffic congestion in Jakarta. The ideal model of policy implementation to be developed in the future is an integrated BRT-based mass transit public transport policy model, not only paying attention to its sustainability but also being just.